2015
DOI: 10.5090/kjtcs.2015.48.5.355
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Congenital Left Ventricular Diverticulum in Adults

Abstract: Isolated congenital left ventricular diverticulum is a rare cardiac malformation. Here, we report the case of a 33-year-old woman who had suffered from recurrent transient ischemic attacks for 6 years. Preoperative cardiac magnetic resonance imaging and computed tomography angiography revealed a diverticulum near the apex. The diverticulum was successfully obliterated by cardiopulmonary bypass. We suggest that isolated congenital left ventricular diverticulum can be easily corrected with a low surgical risk by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Despite the existence of a concise review of the cases reported to date, there is little in the way of a detailed surgical approach. Some authors have reported closure of the diverticulum neck with a patch, with surgical glue closure and plication with aneurysmorrhaphy 8 . Other authors have described their technique as suture reapproximation in a double‐layered fashion with the use of felt, 9 while some describe removal of the outpouching cavity and closure with an in‐situ patch 10 …”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of a concise review of the cases reported to date, there is little in the way of a detailed surgical approach. Some authors have reported closure of the diverticulum neck with a patch, with surgical glue closure and plication with aneurysmorrhaphy 8 . Other authors have described their technique as suture reapproximation in a double‐layered fashion with the use of felt, 9 while some describe removal of the outpouching cavity and closure with an in‐situ patch 10 …”
Section: Commentmentioning
confidence: 99%
“…Some authors have reported closure of the diverticulum neck with a patch, with surgical glue closure and plication with aneurysmorrhaphy. 8 Other authors have described their technique as suture reapproximation in a double-layered fashion with the use of felt, 9 while some describe removal of the outpouching cavity and closure with an in-situ patch. 10 Due to the catastrophic events associated with CLVD, our institution prefers surgical management for patients with symptomatic CLVD.…”
Section: Commentmentioning
confidence: 99%
“…Surgical correction may be considered under some circumstances, including: 1) progressive thinning of the wall of the LVD, 2) right ventricular diverticulum, 3) surgery is required for other reasons, 4) large diverticulum or increasing size over time, 5) development of heart failure, 6) occurrence of complications, 7) systolic dyskinesia or paradoxical bulging, 8) if medical therapy is ineffective, etc. [5, 6]. Surgical treatment of asymptomatic cases is still controversial.…”
mentioning
confidence: 99%